(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Congenital choanal atresia (CCA) is the development failure of the nasal cavity to communicate with nasopharynx. It is an uncommon congenital anomaly of nose with an incidence of approximately 1 in 5000-7000 live births. Choanal atresia is caused by failure of resorption of the nasobuccal membrane during embryonic development. Choanal atresia has a significant association with CHARGE syndrome. Surgical intervention is recommended in the first weeks of life in bilateral cases because this is a life threatening condition. Diagnostic Ten cases of congenital choanla atresia (CCA) was admitted in the department of Otolaryngology & Head-Neck Surgery at Bangabandhu Sheikh Mujib Medical University (BSMMU) with the complaints of intermittent attacks of cyanosis, dyspnea, respiratory distress and history of inability to take feeds. On examination both babies had respiratory distress, mucoid discharge from both nasal cavities. A soft rubber catheter was passed into both nares revealed the diagnosis of CCA which was confirmed by flexible nasoendoscopy. CCA was managed with a nasopharyngeal airway. Surgery is the definitive treatment with two main approaches namely transnasal and transpalatal. We discuss successful management of ten neonates of CCA by endonasal endoscopic approach. Journal of Paediatric Surgeons of Bangladesh (2023) Vol. 14 (1 & 2): 45-48